Investigation of the voltage collapse mechanism in three-phase PWM rectifiers - Han, Xiaoqing (2018)
Three-phase pulse width modulation (PWM) rectifiers are usually designed under the assumption of ideal ac power supply and input inductance. However, non-ideal circuit parameters may lead to a voltage collapse of PWM rectifiers. This paper investigates the mechanism of voltage collapse in three-phase PWM rectifiers. An analytical stability boundary expression is derived by analyzing the equilibrium point of the averaging state space model, which can not only accurately locate the voltage collapse boundary in the circuit parameter domain, but also reveal the essential characteristic of the voltage collapse. Results are obtained and compared with those of the trial-error method and the Jacobian method. Based on the analysis results, the system parameters can be divided into two categories. One of these categories affects the critical point, and other affects only the instability process. Furthermore, an effective control strategy is proposed to prevent a vulnerable system from being driven into the instability region. The analysis results are verified by the experiments.